PENCEGAHAN DAN PENINDAKAN PEMBAJAKAN FILM BERDASARKANPERATURAN UNDANG – UNDANG NOMOR 28 TAHUN 2014TENTANG HAK CIPTA - Anak Agung Gede Agung Indra Prathama; I Gede Mahatma Yogiswara Winatha; Ni Made Novi Maharani; Ni Wayan Devi Muliyanti (Universitas Mahendradatta, 2023)
The purpose of this writing is to examine and explain police efforts to prevent and act against forms of violations of the Law on Copyright Number (28 Year 2014). Due to lack of outreach and lack of seriousness on the part of the government, efforts to prevent piracy are currently ineffective. However, a number of pirates were actively socialized, controlled, and eliminated by the police, which also took other forms of action as needed. In accordance with Law Number (28 of 2014) concerning Copyright, investigations against/the police included complaints and there were also many parties who felt they had lost/harmed. What was done/performed by many government parties through the form of law enforcers, namely the police, as stated in Article 120 concerning complaint offenses. This type of research is empirical and uses sociological and legal research methods. This was done directly by collecting data from prevention as well as taking action against the police based on the number